METHODOLOGICAL PRINCIPLES OF CALENDAR PLANNING BY PROBABILISTIC CHARACTER OF CONSTRUCTION - Altukhova, D. V. (Academic journal Industrial Machine Building Civil Engineering, 2018)
It is defined that the tasks of reducing the cost of construction products should not be solved by saving the direct costs, but due to objective reduction of costs by rationality of the production work organization. It is established that construction works are fulfield in prone to changes of the environment conditions, so not only these factors should be taken into account in the process of construction, but also those that may only be predicted with a certain probability. It was developed the dependence of the work duration calculation both with the usage of a set of construction machine and without its usage by applying the coefficient of the construction project sensitivity to the factors of a changing environment. The proposed calculation allows to reduce the failure risk of the commissioning project terms and provides an opportunity to accelerate the construction process in the given specific conditions. It was carried out the estimation of the coefficient of sensitivity in different local conditions depending on the influence of various factors: weather conditions; provision of material resources; number and qualifications of workers.
Keywords: scheduling; duration of construction; coefficient of sensitivity; probabilistic nature of construction